2023
DOI: 10.1111/1440-1681.13811
|View full text |Cite
|
Sign up to set email alerts
|

Ligustrazine and liguzinediol protect against doxorubicin‐induced cardiomyocytes injury by inhibiting mitochondrial apoptosis and autophagy

Naqi Lian,
Jing Tong,
Weijie Zhu
et al.

Abstract: Preventing or treating heart failure (HF) by blocking cardiomyocyte apoptosis is an effective strategy that improves survival and reduces ventricular remodelling and dysfunction in the chronic stage. Autophagy is a mechanism that degrades intracellular components and compensates for energy deficiency, which is commonly observed in cardiomyocytes of failed hearts. Cardiomyocytes activated by doxorubicin (DOX) exhibit strong autophagy. This study aims to investigate the potential protective effect of ligustrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In this study, we illustrated that DOX treatment not only diminished the viability of H9C2 cells but also heightened cardiomyocyte apoptosis. However, co-treatment with Lig effectively reversed the myocardial damage, aligning with our previous research [ 20 ]. The findings indicate that Lig enhances DOX-induced cardiac function by elevating LVFS and LVEF in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we illustrated that DOX treatment not only diminished the viability of H9C2 cells but also heightened cardiomyocyte apoptosis. However, co-treatment with Lig effectively reversed the myocardial damage, aligning with our previous research [ 20 ]. The findings indicate that Lig enhances DOX-induced cardiac function by elevating LVFS and LVEF in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…and the main cause of cardiac tissue loss and cardiac insufficiency during mitochondria-dependent intrinsic apoptosis [ 36 ]. Studies have reported that Lig has a myocardial protective effect on apoptosis under various pathogenic conditions [ 19 , 20 ]. To assess DOX-induced cardiomyocyte apoptosis, we conducted an immunofluorescence assay and examined apoptotic protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In perspective, the “autophagy flux” can be described as a self-degrading process that involves the sequestration of damaged organelles/proteins into double-membraned autophagosomes that fuse with lysosomes for degradation by resident hydrolases [ 9 ]. In the context of DOX-induced organ toxicity, contradictory findings have emerged regarding autophagy events where both autophagy stimulation [ 10 , 11 ] and inhibition [ 1 , 12 , 13 ] have been described. In rodents, autophagy dysregulation has been implicated in mediating tissue damage [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the upstream regulatory signals responsible for driving the autophagy events, such as the mechanistic target of rapamycin (mTOR) and AMP-activated protein kinase (AMPK), are deregulated by DOX, resulting in marked toxicity [ 1 , 9 ]. On the other hand, the literature revealed that autophagy stimulation can mediate DOX-induced toxicity [ 10 , 11 ]. Hence, further research is needed to determine how autophagy contributes to the toxicity associated with DOX.…”
Section: Introductionmentioning
confidence: 99%